Information System Design for Calculating the Reliability of Electricity Distribution System in Pekalongan Substation Based on Android OS - Aprilian, Salman Muntaqo; Mujaahid, Faaris; Syahputra, Ramadoni; Putra, Karisma Trinanda; Widyasmoro, Widyasmoro (Journal of Electrical Technology UMY, 2020)
Reliability of distribution networks is a factor that greatly affects customers as consumers of electricity. Analyzing and calculating the reliability of distribution networks are determined by the reliability index including SAIFI, SAIDI, CAIDI, and ASAI. On the other hand, smartphone technology is growing rapidly with a variety of applications to help simplify and accelerate human work in several fields of work. This paper delivers the design of an Android-phone-based analytic tool for distribution system reliability index measurement by developing it on Android application software. This application is named KALINDA, stands for Kalkulator Indeks Keandalan (Reliability Index Calculator), and created by using Android Studio IDE. We compare the data result between KALINDA calculations and manual calculations. The results obtained from the KALINDA application are declared to be valid accurate.